Status of Stylosanthes development in other countries.II. Stylosanthes development and utilisation in China and southe-east Asia - Guodao, L; Phaikaew, C; Stür, Werner W. (1997)
Introduction of Stylosanthes species to south-east Asia commenced in 1949 and tended to follow the development of commercial cultivars in Australia. S. guianensis cultivars were introduced to humid and subhumid areas in Malaysia, Indonesia, southern Thailand, Philippines and China. S. humilis, S. hamata and S. scabra were introduced to drier areas in the region such as north-east Thailand, eastern Indonesia and southern China. Anthracnose severely reduced growth and survival of many cultivars used in the region. In 1976, an outbreak of anthracnose in S. humilis prompted a change to S. hamata cv. Verano in Thailand. S. guianensis cv. Schofield was similarly affected in many countries and was replaced by Cook and Graham. Later Cook and recently Graham were similarly affected in many countries and are being replaced by S. guianensis CIAT 184. The most widely used species today are S. hamata cv. Verano, and S. guianensis cv. Graham and CIAT 184. S. hamata is used mainly in north-east Thailand for inclusion in heavily grazed pastures. In 1995, 150 t of seed of S. hamata was produced in Thailand. S. guianensis cv. Graham and CIAT 184 are grown on more than 100 000 ha in monoculture, often associated with perennial tree crops in southern China. It is used as fresh feed for ruminants, or dried and processed as leaf meal. Recently, S. guianensis CIAT 184 has gained popularity in more countries in south-east Asia because of its broad adaptation, potential for multiple uses and high productivity in acid, infertile soils. Prospects for increased use of this species, particularly in smallholder farming systems, are excellent.